Sex and frequency of pain episodes are associated with acute pain trajectories in adolescents with sickle cell disease - Astles, Rachel; Liu, Zihao; Gillespie, Scott E.; Lai, Kristina W.; Maillis, Alexander; Morris, Claudia R.; Lane, Peter A.; Krishnamurti, Lakshmanan; Bakshi, Nitya (Pain reports, 2023)
We report that sex and history of high health care utilization for pain are associated with acute pain trajectories in adolescents with sickle cell disease presenting to the emergency department. AbstractIntroduction/Objective:Acute pain episodes are a major cause of health care utilization (HCU) in sickle cell disease (SCD), and adolescence is associated with increased pain frequency. We sought to determine whether there were differences in acute pain trajectories by sex and frequency of pain episodes among adolescents with SCD who presented to the emergency department (ED).Methods:Retrospective review of electronic health records from a large, multicampus, pediatric SCD program.Results:Of the 113 adolescents included, the mean age was 16.6 (SD 0.9), 41.6% (n = 47) were female, 77.9% (n = 88) had HbSS or a similarly severe genotype, and 43.4% (n = 49) had ≥3 episodes of HCU for pain, which we defined as having history of high HCU for pain. Those with a history of high HCU for pain had higher mean pain intensity scores at presentation, were more likely to receive either intravenous or intranasal opioids, and were more likely to be hospitalized. In a model considering the 3-way interaction between sex, history of high HCU for pain, and follow-up time from the initial pain intensity score, adjusted for opioid per kilogram body weight, and prescription of hydroxyurea, adolescent female patients with high HCU for pain had the slowest decline in pain intensity during treatment for acute pain in the ED.Conclusion:Sex and history of high HCU for pain are associated with acute pain trajectories in adolescents with SCD presenting to the ED. These novel findings should be confirmed in future prospective studies.